2006
DOI: 10.1002/pmic.200600254
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of Agrobacterium tumefaciens response to the vir gene inducer acetosyringone

Abstract: Agrobacterium tumefaciens causes crown gall disease in a wide range of plants by transforming plants through the transfer and integration of its transferred DNA (T-DNA) into the host genome. In the present study, we used two-dimensional gel electrophoresis to examine the protein expression profiles of A. tumefaciens in response to the phenolic compound acetosyringone (AS), a known plant-released virulence (vir) gene inducer. Using mass spectrometry, we identified 11 proteins consisting of 9 known AS-induced Vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 43 publications
2
48
0
Order By: Relevance
“…Although incubation with root segments induced ChvE, AttK, and AttM (all proteins involved in virulence), their experiments detected no induced Ti-plasmid-encoded virulence proteins. Because, for example, VirE2 is a major virulence protein induced by phenolic molecules such as AS (Engstrom et al, 1987;Lai et al, 2006), the results of this study indicate either that vir gene induction did not efficiently occur or that it occurred in only a small percentage of the bacteria.…”
Section: Agrobacterium Transcriptional Profilingmentioning
confidence: 79%
See 1 more Smart Citation
“…Although incubation with root segments induced ChvE, AttK, and AttM (all proteins involved in virulence), their experiments detected no induced Ti-plasmid-encoded virulence proteins. Because, for example, VirE2 is a major virulence protein induced by phenolic molecules such as AS (Engstrom et al, 1987;Lai et al, 2006), the results of this study indicate either that vir gene induction did not efficiently occur or that it occurred in only a small percentage of the bacteria.…”
Section: Agrobacterium Transcriptional Profilingmentioning
confidence: 79%
“…More recently, Lai et al (2006) investigated Agrobacterium proteins induced by the phenolic vir regulon inducer AS. Using two-dimensional gel electrophoresis coupled with mass spectrometry, they identified 11 ASinduced proteins.…”
Section: Agrobacterium Transcriptional Profilingmentioning
confidence: 99%
“…Xu et al (1988) first demonstrated that the excitation and efficient expression of the virulence (Vir) gene, which is necessary for the Ti plasmid of the Agrobacterium transfer into the host cell, was activated by AS trauma-induced molecules. Lai et al (2006) identified 11 AS-induced proteins, which were implicated in Agrobacterium virulence. Therefore, 100 mM AS was added in this experiment.…”
Section: Discussionmentioning
confidence: 99%
“…HspL Co-fractionates with VirB Complexes and Interacts with VirB8, a Key T4SS Assembly Factor-HspL is predicted to be a soluble protein without signal peptide or transmembrane domain (23), and therefore, its co-fractionation with membranes may be due to its association with membrane-associated VirB protein complexes. To assess this possibility, we extracted membrane proteins with the mild detergent DDM and then size-fractionated the DDMextracted proteins by SEC (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple ␣-Hsp genes are present in rhizobial bacteria (19 -21) including A. tumefaciens containing at least four members of ␣-Hsp genes (hspC; hspL; hspAT1; hspAT2) (22). The latter three were induced by heat shock (22), whereas only hspL was up-regulated by the virulence gene inducer acetosyringone (AS) (18,23).…”
mentioning
confidence: 99%